Development of Ternate Language Vocabulary Games Using Wordwall at SMP Islam 1 Ternate - Roni Kurniawan; Sasmayunita (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
The objective of this research is to develop an educational game of Ternate language vocabulary using the Wordwall application to enhance interest and learning outcomes in Ternate local language learning at SMP Islam 1 Ternate. The study was guided by Thiagarajan's 4-D model, which consists of the stages of Define, Design, Develop, and Disseminate. This model structured the development of the educational game for vocabulary in Ternate language, ensuring that it addressed students' needs, was successfully designed and validated, and was implemented in the classroom. The study’s participants were 25 students from the eighth grade, specifically from class VIII-A. The data was analysed using a quantitative descriptive technique, expressed as the mean value of the validation scores. In regard to the feasibility of the educational game, the results of the verb feasibility test conducted by material experts yielded a score of 95.5%, while the test administered by media experts returned a score of 92.25%. In the case of vocabulary games, the results of the feasibility test of nouns by material experts reached 96%, while the figure from media experts was 94%. The results of the feasibility test for the adjective game conducted by the material expert reached 92.5%, while the test conducted by the media expert reached 90.5%. The learning outcome test for Ternate language using this educational game reached 100% classical completeness with an average score of 86.72. These results demonstrate that this educational game is highly feasible for use in language learning and has the potential to significantly enhance student learning outcomes.